Analysis of Factors Influencing the Performance of Tax Center Volunteers: A Case Study at Jember State Polytechnic - Wijayanti, Rahma Rina; Ardhiarisca, Oryza; Sutantio, R. Alamsyah; Harkat, Avisenna; Ghozali, Nur Azizah Wandinia; Ardiansyah, Diki; Pratiwi, Arti Febriani (P3M Politeknik Negeri Jember, 2025)
Performance is the output of activities carried out by tax volunteers. In this case, tax volunteers are tasked with filling out annual tax returns for taxpayers. These activities have an impact on increasing state revenues. This study is to determine the factors that need to be improved in the performance of tax volunteers. This research method is quantitative research and regression analysis. The research results show that the self-assessment system, motivation, and work discipline variables significantly influenced the performance of tax volunteers. Meanwhile, the variables of training materials and training methods do not significantly influence the performance of tax volunteers. These findings can be applied to analyze the factors that affect the performance of Tax Center volunteers at Jember State Polytechnic. Their significance factors contribute to achieving a sustainable program at Tax Center Jember State Polytechnic.